2016
DOI: 10.1186/s12917-016-0886-2
|View full text |Cite
|
Sign up to set email alerts
|

Strong inflammatory responses and apoptosis in the oviducts of egg-laying hens caused by genotype VIId Newcastle disease virus

Abstract: BackgroundNewcastle disease virus (NDV) can cause serious damage to the reproductive tracts of egg-laying hens and leads to egg production and quality reduction. However, the mechanism of severe pathological damage in the oviducts of egg-laying hens after NDV infection has not been fully elucidated. In this study, the correlation between the primary pathological lesions and viral load in the oviducts of egg-laying hens infected with the velogenic genotype VIId NDV strain was evaluated by pathological observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…IL-1β is the central mediator of the inflammatory response, and neutralizing IL-1β using a specific antibody has been shown to reduce the inflammatory response to influenza A virus [8]. Studies have shown that following infection with NDV virulent strains, various organs exhibited varying degrees of exudative inflammation and inflammatory factors, such as IL-1β, IL-6, IL-18 and IFNβ, which were released in large quantities, resulted in high animal mortality rates, and were also observed in Experiment 1 of this study [1,2,45]. Alternatively, infection with lentogenic strains resulted in only mild non-lifethreatening clinical symptoms, with all chickens eventually recovering.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…IL-1β is the central mediator of the inflammatory response, and neutralizing IL-1β using a specific antibody has been shown to reduce the inflammatory response to influenza A virus [8]. Studies have shown that following infection with NDV virulent strains, various organs exhibited varying degrees of exudative inflammation and inflammatory factors, such as IL-1β, IL-6, IL-18 and IFNβ, which were released in large quantities, resulted in high animal mortality rates, and were also observed in Experiment 1 of this study [1,2,45]. Alternatively, infection with lentogenic strains resulted in only mild non-lifethreatening clinical symptoms, with all chickens eventually recovering.…”
Section: Discussionsupporting
confidence: 69%
“…Newcastle disease (ND) is a highly contagious disease of poultry that leads to acute fever and sepsis and is caused by the Newcastle disease virus (NDV). This virus consists of a negative-sense, single-stranded RNA genome of approximately 15 190 nucleotides that encodes the structural proteins NP, P, M, F, HN, and L and the non-structural proteins V and W. Infection with virulent strains of NDV causes a strong immune response, with different organs expressing varying degrees of exudative inflammation, resulting in the release of large quantities of inflammatory factors, such as IL-1β, IL-6, IL-18, and IFN-β [1,2]. Thus, exploring the mechanisms underlying the NDV-induced inflammatory response can aid in understanding the pathogenesis of Newcastle disease.…”
Section: Introductionmentioning
confidence: 99%
“…Infectious factors, such as avian leukosis virus [8], Marek's disease virus [9], and NDV [10], affect reproductive performance. Although, NDV replicates in the ovary and oviduct [11], causing severe inflammation and apoptosis, and result into decreased egg production [12][13][14] and fertility rates [15], the pathologic effects of NDV on the male reproductive system are yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The innate immune response is the first line of defence against invading viruses and stimulates a specific mucosal and humoral immune response [18]. In NDV infection, after the detection of viruses by pattern recognition receptors (PRRs), complex host-pathogen interaction pathways direct an intense inflammatory response to inhibit viral replication [14,19] and elevate plasma glucocorticoids [20]. These pro-inflammatory cytokines and their crosstalk with hormones shape the immune system to control the potential harmful effects and the return of homeostasis after the clearance of a pathogen [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation